2020
DOI: 10.1093/hmg/ddaa163
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of foxc1 genes in zebrafish results in dosage-dependent phenotypes overlapping Axenfeld-Rieger syndrome

Abstract: The Forkhead Box C1 (FOXC1) gene encodes a forkhead/winged helix transcription factor involved in embryonic development. Mutations in this gene cause dysgenesis of the anterior segment of the eye, most commonly Axenfeld-Rieger syndrome (ARS), often with other systemic features. The developmental mechanisms and pathways regulated by FOXC1 remain largely unknown. There are two conserved orthologs of FOXC1 in zebrafish, foxc1a and foxc1b. To further examine the role of FOXC1 in vertebrates, we generated foxc1a an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…native start sites (Figure S3), both mutations occur in the N-terminal transactivation domain where even small deletions profoundly reduce FOXC1 activity [75]. Furthermore, our novel mutations overlap previously published foxc1 null mutations (el542, el543, and el620 [60]) and phenocopy loss-of-function mutations in the Forkhead box DNA-binding domain [76]. For these reasons, we believe that the novel foxc1 mutations provide good models for foxc1 loss-of-function.…”
Section: Generation Of Foxc1a and Foxc1b Zebrafish Mutantssupporting
confidence: 68%
See 2 more Smart Citations
“…native start sites (Figure S3), both mutations occur in the N-terminal transactivation domain where even small deletions profoundly reduce FOXC1 activity [75]. Furthermore, our novel mutations overlap previously published foxc1 null mutations (el542, el543, and el620 [60]) and phenocopy loss-of-function mutations in the Forkhead box DNA-binding domain [76]. For these reasons, we believe that the novel foxc1 mutations provide good models for foxc1 loss-of-function.…”
Section: Generation Of Foxc1a and Foxc1b Zebrafish Mutantssupporting
confidence: 68%
“…Firstly, previous studies whereby foxc1b was knocked down via morpholino oligonucleotides failed to resolve a phenotype despite foxc1a knockdown resulting in microphthalmia, somitic delay, and intracranial hemorrhage [ 46 , 66 , 86 ]. Furthermore, foxc1b mutants have also been described without resolving a phenotype [ 60 , 76 ]. Our findings demonstrate that foxc1b is required for cardiac situs in isolation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without question, both proteins show dosage sensitivity, as minute deletions of either Foxc1 or Pitx2 lead to ARS by way of haploinsufficiency, and a previous study reported an ARS phenotype that may also result from the genetic duplication of Foxc1 (Berry et al, 2006). In addition, zebrafish carrying a heterozygous Foxc1 gene deletion mutation showed ocular defects from haploinsufficiency consistent with the ocular manifestations in their human counterparts (Ferre-Fernández et al, 2020). Similarly, an assessment of the requirements for Pitx2 showed that heterozygotes for either hypomorphic or null alleles in the Pitx2 gene have eye abnormalities consistent with ARS, indicating a Pitx2 dosage requirement for eye development in mice (Gage et al, 1999a,b).…”
Section: Dosage Effectsmentioning
confidence: 81%
“…By 3 days post fertilization (dpf), rudimentary structures of the anterior segment are present and will continue to develop through the first month of life. Zebrafish with homozygous mutations in foxc1a and foxc1b display underdeveloped or absent anterior segments beginning around 3 dpf [ 39 ]. Additional ocular phenotypes, including microphthalmia ( Figure 1 I,J) and coloboma are often observed in double homozygous foxc1a / foxc1b zebrafish, which are typically not observed in ARS patients.…”
Section: Ocular Related Phenotypes In Foxc1a and Foxc1b Mutantsmentioning
confidence: 99%